Applications of Coarse-Grained Models in Metabolic Engineering - Doan, Dieu Thi; Hoang, Manh Dat; Heins, Anna-Lena; Kremling, Andreas (Frontiers in Molecular Biosciences, 2022)
Mathematical modeling is a promising tool for better understanding of cellular processes. In recent years, the development of coarse-grained models has gained attraction since these simple models are able to capture and describe a broad range of growth conditions. Coarse-grained models often comprise only two cellular components, a low molecular component as representative for central metabolism and energy generation and a macromolecular component, representing the entire proteome. A framework is presented that presents a strict mass conservative model for bacterial growth during a biotechnological production process. After providing interesting properties for the steady-state solution, applications are presented 1) for a production process of an amino acid and 2) production of a metabolite from central metabolism.